2010
DOI: 10.1007/s10508-010-9609-0
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sex Guilt in the Relationship Between Culture and Women’s Sexual Desire

Abstract: A large body of literature demonstrates that East Asian women report lower sexual desire than Caucasian women. Although most studies have explained these differences by referring to general culture-linked differences in sexual conservatism, none have examined the potential role of specific constructs such as sex guilt. The goals of the current study were to examine the supposition that sexual conservatism mediates the relationship between culture and sexual desire, and to explore the potential mediating role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(50 citation statements)
references
References 56 publications
1
42
2
5
Order By: Relevance
“…As an alternative to unidimensional models, which put mainstream culture and heritage culture at opposite ends of a continuum, bidimensional models independently assess endorsement of both mainstream and heritage cultures (Brotto et al, 2005;Meston & Ahrold, 2010;Woo & Brotto, 2008;Woo et al, 2011). Bidimensional models have two core assumptions.…”
Section: Models Of Acculturationmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative to unidimensional models, which put mainstream culture and heritage culture at opposite ends of a continuum, bidimensional models independently assess endorsement of both mainstream and heritage cultures (Brotto et al, 2005;Meston & Ahrold, 2010;Woo & Brotto, 2008;Woo et al, 2011). Bidimensional models have two core assumptions.…”
Section: Models Of Acculturationmentioning
confidence: 99%
“…Previous research suggested that in general, high endorsement of heritage culture (enculturation) is associated with more conservative sexual values, narrower repertoire of sexual behaviors, less sexual satisfaction, and less frequency in sexual activities; whereas, high endorsement of U.S. mainstream culture (acculturation) is related with more open attitudes towards sex, increased pleasure and arousal from sexual activities, less sexual guilt, and more sexual communication (Brotto et al, 2005;Morton & Gorzalka, 2013;Woo & Brotto, 2008;Woo, Brotto, & Gorzalka, 2011), which potentially leads to higher relationship and sexual satisfaction. Lee, Oyserman, & Bond, 2010;Marian & Neisser, 2000;Matsumoto, Anguas-Wong, & Martinex, 2008;Oyserman & Lee, 2008;Trafimow, Silverman, Fan, & Law, 1997;Verkuyten & Pouliasi, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual anxiety has long been thought to play an important role in the sexual dysfunction of both men and women (Aluja, 2004;Beggs, Calhoun, & Wolchik, 1987;Hensel, Fortenberry, O'Sullivan, & Orr, 2011), and at extreme levels can become a clinically disordered experience leading to sexual dysfunction and requiring therapeutic attention (e.g., Everaerd & Dekker, 1982;Mccabe, 1992;Munjack, 1984;Nemetz, Craig, & Reith, 1978;White, Fichtenbaum, & Dollard, 1967). Sexual guilt has been implicated in decreased sexual drive and satisfaction and increased sexual dysfunction (Cado & Leitenberg, 1990;Darling, Davidson, & Passarello, 1992;Galbraith, 1969;Merrell, 2009;Morokoff, 1985;Nobre & Pinto-Gouveia, 2006;Woo, Brotto, & Gorzalka, 2011), and less sexual behavior including sexual intercourse (Love, Sloan, & Schmidt, 1976). Considering lower sexual frequency has been found to be related to higher rates of divorce (Yabiku & Gager, 2009) the presence of sexual guilt could create marriage instability.…”
Section: Sexual Guilt and Anxiety Of Muslimsmentioning
confidence: 99%
“…Sexual anxiety has long been thought to play an important role in the sexual dysfunction of both men and women (Aluja, 2004;Beggs, Calhoun, & Wolchik, 1987;Hensel, Fortenberry, O'Sullivan, & Orr, 2011), and at extreme levels can become a clinically disordered experience leading to sexual dysfunction and requiring therapeutic attention (e.g., Everaerd & Dekker, 1982;Mccabe, 1992;Munjack, 1984;Nemetz, Craig, & Reith, 1978;White, Fichtenbaum, & Dollard, 1967). Sexual guilt has been implicated in decreased sexual drive and satisfaction and increased sexual dysfunction (Cado & Leitenberg, 1990;Darling, Davidson, & Passarello, 1992;Galbraith, 1969;Merrell, 2009;Morokoff, 1985;Nobre & Pinto-Gouveia, 2006;Woo, Brotto, & Gorzalka, 2011), and less sexual behavior including sexual intercourse (Love, Sloan, & Schmidt, 1976). Considering lower sexual frequency has been found to be related to higher rates of divorce (Yabiku & Gager, 2009) the presence of sexual guilt could create marriage instability.…”
Section: Sexual Guilt and Anxiety Of Muslimsmentioning
confidence: 99%